Platycodon grandiflorum Root Protects against Aβ-Induced Cognitive Dysfunction and Pathology in Female Models of Alzheimer's Disease - Yunkwon Nam; Soo Jung Shin; Yong Ho Park; Min-Jeong Kim; Seong Gak Jeon; Hyewon Lee; Yeji Choi; Tae-Jin Kim; Seong Min Shin; Jwa-Jin Kim; Doo-Han Yoo; Hyung Don Kim; et al. (MDPI AG, 2021)
Alzheimer's disease (AD) is a devastating neurodegenerative disease characterized by irreversible cognitive dysfunction. Amyloid beta (Aβ) peptide is an important pathological factor that triggers the progression of AD through accumulation and aggregation, which leads to AD-related pathologies that consequently affect cognitive functions. Interestingly, several studies have reported that Platycodon grandiflorum root extract (PGE), besides exhibiting other bioactive effects, displays neuroprotective, anti-neuroinflammatory, and cognitive-enhancing effects. However, to date, it is not clear whether PGE can affect AD-related cognitive dysfunction and pathogenesis. Therefore, to investigate whether PGE influences cognitive impairment in an animal model of AD, we conducted a Y-maze test using a 5XFAD mouse model. Oral administration of PGE for 3 weeks at a daily dose of 100 mg/kg significantly ameliorated cognitive impairment in 5XFAD mice. Moreover, to elucidate the neurohistological mechanisms underlying the PGE-mediated alleviative effect on cognitive dysfunction, we performed histological analysis of hippocampal formation in these mice. Histopathological analysis showed that PGE significantly alleviated AD-related pathologies such as Aβ accumulation, neurodegeneration, oxidative stress, and neuroinflammation. In addition, we observed a neuroprotective and antioxidant effect of PGE in mouse hippocampal neurons. Our findings suggest that administration of PGE might act as one of the therapeutic agents for AD by decreasing Aβ related pathology and ameliorating Aβ induced cognitive impairment.